Translating Evidence from Clonal Hematopoiesis to Cardiovascular Disease: A Systematic Review - Vaccarezza, Mauro; Papa, V.; Marracino, L.; Fortini, F.; Rizzo, P.; Campo, G.; Vieceli Dalla Sega, F (MDPI AG, 2020)
Some random mutations can confer a selective advantage to a hematopoietic stem cell. As a result, mutated hematopoietic stem cells can give rise to a significant proportion of mutated clones of blood cells. This event is known as “clonal hematopoiesis.” Clonal hematopoiesis is closely associated with age, and carriers show an increased risk of developing blood cancers. Clonal hematopoiesis of indeterminate potential is defined by the presence of clones carrying a mutation associated with a blood neoplasm without obvious hematological malignancies. Unexpectedly, in recent years, it has emerged that clonal hematopoiesis of indeterminate potential carriers also have an increased risk of developing cardiovascular disease. Mechanisms linking clonal hematopoiesis of indeterminate potential to cardiovascular disease are only partially known. Findings in animal models indicate that clonal hematopoiesis of indeterminate potential-related mutations amplify inflammatory responses. Consistently, clinical studies have revealed that clonal hematopoiesis of indeterminate potential carriers display increased levels of inflammatory markers. In this review, we describe progress in our understanding of clonal hematopoiesis in the context of cancer, and we discuss the most recent findings linking clonal hematopoiesis of indeterminate potential and cardiovascular diseases.